Effect of Deficit Irrigation on Physico-chemical Characteristics in Various Kiwifruit (Actinidia deliciosa Chev.) Cultivars - Pratima, Preet; Sharma, N.; Sagar, Heerendra (International Journal of Bio-resource and Stress Management, 2018)
The kiwifruit vines probably die more often because of water stress than any other problems. There is a need to screen out such cultivars which have potential to grow in water scarce areas. With this objective, the present investigation was carried out in the experimental area of Department of Fruit Science, Dr. Y. S. Parmar University of Horticulture and Forestry Nauni during 2011–2012. Two irrigation levels viz., Irrigation at 80% field capacity (standard irrigation-SI) and irrigation at 60% FC (deficit irrigation-DI) with four replications were given in five cultivars viz., Allison, Hayward, Abbott, Monty and Bruno. The experiment was arranged in Randomized Block Design. The fruit quality characteristics were significantly variable among the cultivars and were also influenced by the irrigation levels. Under SI the fruit quality in terms of fruit weight, firmness and ascorbic acid content was found to be highest in cultivar Bruno among all these mentioned cultivars whereas, the titratable acidity under SI was found to be highest in cultivar Monty and least in Allison. The DI resulted in reduction in all these attributes and the percent reduction is found to be highest in cultivar Hayward and least in Bruno. The parameters like total soluble solids (TSS) and sugars were found to be highest in cultivar Allison and least in Monty under SI but the percent increase in these characteristics were found to be highest in cultivar Hayward and least in cultivar Bruno. The Bruno cultivar was found to be suitable under deficit irrigation and therefore, it should be preferred for cultivation under water scarce areas.